The Yarrowia lipolytica PAH1 homologue contributes but is not required for triacylglycerol biosynthesis during growth on glucose. Issue 1 (7th January 2020) - Ukey, Rahul; Carmon, Taylor; Hardman, Derell; Hill, Na'Taja; Fakas, Stylianos
Abstract: The PAH1 ‐encoded phosphatidate phosphatase (PAP) catalyzes the Mg 2+ ‐dependent dephosphorylation of phosphatidate to produce diacylglycerol, which can be acylated to form triacylglycerol (TAG). In the model oleaginous yeast Yarrowia lipolytica, TAG is the major lipid produced, and its biosynthesis requires a continuous supply of diacylglycerol, which can be provided by the PAP reaction. However, the regulation of Pah1 has not been studied in detail in Y. lipolytica, and thus its contribution to the biosynthesis of TAG in this yeast is not well understood. In this work, we examined the regulation of the PAH1 ‐mediated PAP activity and Pah1 abundance and localization in cells growing on glucose. We found that Pah1 abundance and localization were regulated in a growth‐dependent manner, yet the loss of Pah1 did not have a major effect on PAP activity. We also examined the effects of the Y. lipolytica pah1 Δ mutation on cell physiology and lipid biosynthesis. The lack of Pah1 in the pah1 Δ mutant resulted in a moderate decrease in TAG levels and an increase in phospholipid levels. These results showed that Pah1 contributed to TAG biosynthesis in Y. lipolytica but also suggested the presence of other activities in the pah1 Δ mutant that compensate for the loss of Pah1. Also, the levels of linoleic acid were elevated in pah1 Δ cells with a concomitant decrease in the oleic acid levels suggesting that the pah1 Δ mutation affected the biosynthesis of fatty acids.